Rescate de la identidad gastronómica de Carpuela y El Chota para el fortalecimiento del turismo del cantón Ibarra - Escobar Hernández, Lizbeth Victoria (2023)
The purpose of this research is to carry out an app for cell phones or electronic devices with an android system of gastronomic information from the communities of Carpuela and El Chota, with the purpose of rescuing the gastronomy of these places. It is important to notice that previous studies of (Guerrero 2017) and (Salazar,Parra) were used in order to have a reference to the creation of the App for Android devices. Also a non-experimental, descriptive investigation was carried out. All of the investigation was collected from primary sources. Surreys and interviews were applied to determine the problem to observe, analyze and diagnose the gastronomy of Imbabura province specially on the communities of Carpuela and El Chota that have been lost over the years from generation to generation, with the purpose that gastronomy of these towns can not become extinct. Today technology is advancing in a faster way and it is suitable to implement the app, In that order this application can be download on smartphones to attract and promote tourism in Ibarra canton, particularly in the communities of Carpuela and El Chota.